Highlighting of quorum sensing lux genes and their expression in the hydrothermal vent shrimp Rimicaris exoculata ectosymbiontic community. Possible use as biogeographic markers. - Simon Le Bloa; Lucile Durand; Valérie Cueff-Gauchard; Josiane Le Bars; Laure Taupin; Charlotte Marteau; Alexis Bazire; Marie-Anne Cambon-Bonavita (PLoS ONE, 2017)
Rimicaris exoculata is a caridean shrimp that dominates the fauna at several hydrothermal vent sites of the Mid-Atlantic Ridge. It has two distinct and stable microbial communities. One of these epibiontic bacterial communities is located in the shrimp gut and has a distribution and role that are poorly understood. The second colonizes its enlarged gill chamber and is involved in host nutrition. It is eliminated after each molt, and has colonization processes reminiscent of those of a biofilm. The presence and expression of genes usually involved in quorum sensing (QS) were then studied. At four sites, Rainbow, TAG, Snake Pit and Logatchev, two lux genes were identified in the R. exoculata epibiontic community at different shrimp molt stages and life stages. RT-PCR experiments highlighted lux gene expression activity at TAG, Snake Pit and Rainbow vent sites. Their potential QS activity and their possible roles in epibiont colonization processes are discussed. Moreover, phylogenetic analysis has shown the presence of three clades for luxS (Epsilonproteobacteria) and four clades for luxR (Gammaproteobacteria) genes, each clade being restricted to a single site. These genes are more divergent than the 16S rRNA one. They could therefore be used as biogeographical genetic markers.